2021
DOI: 10.1017/s1368980021003104
|View full text |Cite
|
Sign up to set email alerts
|

The effect of food insecurity during college on graduation and type of degree attained: evidence from a nationally representative longitudinal survey

Abstract: Objective: To examine the effect of food insecurity during college on graduation and degree attainment. Design: Secondary analysis of longitudinal panel data. We measured food insecurity concurrent with college enrollment using the 18-question USDA Household Food Security Survey Module. Educational attainment was measured in 2015-2017 via two questions about college completion and highest degree attained. Logistic and multinomial-logit models adjusted for sociodemographic characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 35 publications
(65 reference statements)
2
46
1
Order By: Relevance
“…A recent study found food-insecure college students have 42% lower odds of graduating (50). These findings were pronounced for first-generation college students, with less than half who experienced FI finishing their education (50). This decline in graduation rate may be attributed to poor academic performance, including lower ability to focus in the classroom, which is amplified among food-insecure students (16,31).…”
Section: A Detriment To Student Successmentioning
confidence: 97%
See 2 more Smart Citations
“…A recent study found food-insecure college students have 42% lower odds of graduating (50). These findings were pronounced for first-generation college students, with less than half who experienced FI finishing their education (50). This decline in graduation rate may be attributed to poor academic performance, including lower ability to focus in the classroom, which is amplified among food-insecure students (16,31).…”
Section: A Detriment To Student Successmentioning
confidence: 97%
“…However, FI impacts the chance of obtaining a degree (49). A recent study found food-insecure college students have 42% lower odds of graduating (50). These findings were pronounced for first-generation college students, with less than half who experienced FI finishing their education (50).…”
Section: A Detriment To Student Successmentioning
confidence: 99%
See 1 more Smart Citation
“…FI is a public health problem that needs attention. Particularly in university students, FI has been positively associated with lower overall self-reported health [13,15,36], more inadequate eating behaviors (such as lower fruit and vegetable intake [13,27,48], no daily breakfast and evening meal consumption [47]), fewer days of physical activity [47,48], fewer days of enough sleep [48], poor sleep quality [33], disordered eating [33], lower grade point average (GPA) [13,15,32,33,36,49,50], lower academic progress [15], difficulty concentrating in class [13], withdrawing from class or the institution [13], lower likelihood of college graduation and obtaining a bachelor's degree or graduate/professional degree [51], poor mental health [47,49], stress [32,33,47] and depressed mood [32,47], and higher BMI [48].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, food-insecure college students are more likely to take a reduced course load, neglect coursework, and consider dropping out of college than their food-secure peers (Phillips, McDaniel, & Croft, 2018). Given its associations with these indicators of academic disruption, food insecurity during college may also be associated with longer time-todegree and lower graduation rates (Wolfson, Insolera, Cohen, & Leung, 2021). The relationship with academic performance appears to be explained by the elevated depression, anxiety, stress, and hopelessness associated with food insecurity (Martinez, Frongillo, Leung, & Ritchie, 2020;Raskind, Haardörfer, & Berg, 2019).…”
mentioning
confidence: 99%